Plant growth and health promoting bacteria - Maheshwari, D. K. (Microbiology Monographs, 2010)
To cope with the increasing problems created by agrochemicals such as plant fertilizers, pesticides and other plant protection agents, biological alternatives have been developed over the past years. These include biopesticides, such as bacteria for the control of plant diseases, and biofertilizer to improve crop productivity and quality. Especially plant growth promoting rhizobacteria (PGPR) are as effective as pure chemicals in terms of plant growth enhancement and disease control, in addition to their ability to manage abiotic and other stresses in plants. The various facets of these groups of bacteria are treated in this Microbiology Monograph, with emphasis on their emergence in agriculture. Further topics are Bacillus species that excrete peptides and lipopeptides with antifungal, antibacterial and surfactant activity, plant-bacteria-environment interactions, mineral-nutrient exchange, nitrogen assimilation, biofilm formation and cold-tolerant microorganisms.